Research on the Use of Sweet Potato Flour as Wheat Substitute in Cake Making - Rohaman, M. Maman; -, Novianis; Djubaedah, Endah (Balai Besar Industri Agro, 1988)
A study to substitute sweet potato flour for wheat flour in cake making had been carried out. The acceptability of substitution was analyzed by panel test using cake made from teo kinds of wheat flou and various percentages of substitution (0,2040 and 60%). The product were also analyzed chamically and organoleptically. The result showed that the use of sweet potato flour significantly affect water, protein and sugar content of the cake. Twenty percent of sweet potato flour substitution showed significant different with those of 40 and 60%. Organoleptic test showed that the 20% substitution is acceptable